Three year outcomes following positive cross match renal transplantation despite failure to convert to Negative Flow Cross Match after Desensitization - Patel, Shree; Benken, Jamie; Thielke, Patricia West; Akkina, Sanjeev; Benedetti, Enrico; Thielke, James (Journal of Clinical Nephrology, 2018)
Desensitization allows successful transplantation of patients with a positive crossmatch (PXM) against their live donor. We evaluated outcomes following PXM renal transplant despite failure to convert to negative flow cytometric crossmatch (FCXM) after desensitization. Patients that underwent desensitization before PXM transplant between 1/1/00 and 11/1/11 were identified for analysis. Patients who received a transplant despite failure to convert to negative FCXM were identified as the not converted group. Patients who converted to negative FCXM after desensitization comprised the converted group control arm. 108 patients were desensitized before PXM transplant, (not converted group=42; converted group=66). Mean eGFR was comparable between groups at all time points, and 3-year eGFR was 57.8 mL/min vs. 57.1 mL/min, p=0.91. Patients with eGFR < 30mL/min at 3 years did not differ significantly (28% vs. 14%, p=0.15). Biopsy-proven rejection rates were numerically higher within the not converted group for each type of rejection and time point, but the values did not differ significantly. Opportunistic infections rates were comparable. Patient survival (95% vs. 91%) and death-censored allograft survival (84% vs. 95%, p=0.07) were similar between arms at 3 years post-transplant.